2010
DOI: 10.1159/000312633
|View full text |Cite
|
Sign up to set email alerts
|

CD8 and CD103 Are Highly Expressed in Asthmatic Bronchial Intraepithelial Lymphocytes

Abstract: Background: Although characteristics of intraepithelial lymphocytes (IELs) in mucosal immunity have been well defined in the intestine, bronchial IELs have been little investigated. Recently, we showed that bronchial IELs have a distinct function that partly resembles that of intestinal IELs; however, surface antigen expression of bronchial IELs and the relationship of that expression to airway disease have not been studied. Methods: We analyzed phenotypic profiles of human bronchial IELs and lamina propria ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…However, our findings in this group are comparable to data published by Hirosako et al, who have meticulously analyzed CD103 + expression by intraepithelial T cells in human bronchi (third to fifth generation) in a patient group that is demographically very similar to our cohort (14,16). They showed that a range of 74% to 94% of intraepithelial CD8 + cells expressed CD103, whereas only 8% to 25% of lamina propria T cells expressed CD103.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, our findings in this group are comparable to data published by Hirosako et al, who have meticulously analyzed CD103 + expression by intraepithelial T cells in human bronchi (third to fifth generation) in a patient group that is demographically very similar to our cohort (14,16). They showed that a range of 74% to 94% of intraepithelial CD8 + cells expressed CD103, whereas only 8% to 25% of lamina propria T cells expressed CD103.…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemistry confirmed that most lung CD103 + CD3 + CD8 + T cells were indeed located intraepithelially above the basement membrane of the small airways ( Figure 1C), as was previously published (13)(14)(15)(16).…”
Section: Human Lung Cd8 + T Cells Expressing αE Integrin Are Ielssupporting
confidence: 86%
See 1 more Smart Citation
“…Previously, SONT et al [34] found that despite ICS treatment, CD8+ T-cell infiltration might persist in asthma patients and that CD8+, but not CD4+, cells are associated with BHR [34] and lung function decline [35], and recently, HIROSAKO et al [8] showed that CD8 and CD103 (ligand for E-cadherin) are highly expressed in asthmatic bronchial intraepithelial lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin, the major cadherin expressed in epithelial cells, is an adhesion molecule that is able to establish and stabilise cellular junctions between adjacent cells in the presence of Ca 2+ [7] and is coded by the CDH1 gene on chromosome 16q22.1. HIROSAKO et al [8] suggested that human bronchial intraepithelial lymphocytes have roles distinct from subsets of other lymphocytes, and that CD8+ cells and CD103+ (ligand of Ecadherin) cells have potentially important functions in the bronchial epithelium.…”
mentioning
confidence: 99%